Domestic politics of the United States of America under President James Monroe (1817-1825) - AlRikabi, Ass. Prof. Dr. Ahmed Mrayih ALMnesrawi (Thi Qar Arts Journal, 2022)
During the reign of President James Monroe, the United States of America witnessed a clear stability in its domestic policy, as he had a major role in strengthening the union, bringing the political parties closer together, and deepening national unity, until his reign was called (the era of good feelings), and the American people gave him their confidence twice, and elected him to the post of president For the period from (1817-1825). As the union expanded by including five new states, in addition to overcoming the economic crisis that the country witnessed in 1819, achieving economic prosperity, protecting the national industry, and strengthening the central government.